2020
DOI: 10.1021/acs.langmuir.0c01476
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations and Density Functional Theory on Unraveling Photoresponsive Behavior of Wormlike Micelles Constructed by 12-2-12·2Br and trans-ortho-Methoxy Cinnamate

Abstract: Photoresponsive systems with controllable self-assembly morphologies and adjustable rheological properties have attracted widespread interest by researchers in the past few years. Among them, the photoresponsive systems consisting of orthomethoxycinnamic (OMCA) and Gemini surfactants are endowed with rich self-assemblies with different states and in different scales including spherical micelles, wormlike micelles, vesicles, aqueous two-phase system (ATPS), etc. All these self-assemblies display excellent photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Previous studies have shown that the structure degradation of wormlike micelles is mainly caused by the changes in the interaction between cinnamates and surfactants because of the photoisomerization of light-sensitive molecules from trans isomers to cis isomers. As discussed above, the binding energies of 12-3-12·2Br – and cis -MCA with different substitution positions are smaller than those of systems containing trans -MCAs. After UV irradiation, the cinnamate derivatives are transformed from trans isomers to cis isomers, and the cis isomers tend to escape from micelles to the solvent, which is unfavorable to the existence of wormlike micelles with long flexible structures.…”
Section: Results and Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Previous studies have shown that the structure degradation of wormlike micelles is mainly caused by the changes in the interaction between cinnamates and surfactants because of the photoisomerization of light-sensitive molecules from trans isomers to cis isomers. As discussed above, the binding energies of 12-3-12·2Br – and cis -MCA with different substitution positions are smaller than those of systems containing trans -MCAs. After UV irradiation, the cinnamate derivatives are transformed from trans isomers to cis isomers, and the cis isomers tend to escape from micelles to the solvent, which is unfavorable to the existence of wormlike micelles with long flexible structures.…”
Section: Results and Discussionmentioning
confidence: 93%
“…TEM observation shows (Figure a,b) that the average size of spherical micelles is approximately 40 nm, while the length of wormlike micelles exceeds several microns. The negatively charged cinnamate ions interact with the positively charged Gemini surfactant micelles by electrostatic attraction and promote the growth of micelles to some extent, which should be the primary cause for the micellar growth. With the further addition of cinnamates, the single phase of wormlike micelles would be transformed into coexisting two phases in the macroscopic level (II, ATPS), as exhibited in Figure c.…”
Section: Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations